Foot orthoses improve kinematic measurement in young women with biomechanical abnormality - Maria Regina Rachmawati; Angela BM Tulaar; Muctarudin Mansyur; Ferial Hadipoetro Idris; Ismail Ismail; Ratna Darjanti Haryadi (Universa Medicina, 2015)
BACKGROUND Foot pronation causes biomechanical abnormalities in the form of functional leg-length disparity. Foot orthoses are often used in the treatment of abnormal pronation. The aim of the study was to evaluate the effect of foot orthoses on abnormal kinematic chain the differences of pelvic height, step length, and walking distance on walking test in young women with biomechanical abnormality.